The Curial Exequies for Edward I and Edward III - Ullmann, Walter (The journal of ecclesiastical history, 1955)
It is not generally known that solemn exequies were performed for Edward I at Poitiers in the presence of the pope, Clement V; that these exequies were the first exequies held in the curia for a king; that they supplied the model for the corresponding ceremonial in the office for the dead laid down in Ordo Romanus XIV which was composed by cardinal James Gaetano Stefaneschi; and that, furthermore, the liturgical details of a canonisation ceremony shown in the same Ordo Romanus (OR.) were modelled on the ceremonial actually observed at the canonisation of St. Thomas Cantelupe of Hereford in 1320. Lastly, attention must be directed to the apparently also unknown exequies solemnly performed for Edward III at Anagni on 3 September 1377, again in the presence of the pope, Gregory XI.